Treatment of Serologically Confirmed Brucellosis in Paholpolpayuhasena Hospital - Wiangcharoen, Rakpong (Journal of Health Science of Thailand, 2018)
Brucellosis remains a major zoonotic disease. There are very few reported cases inThailand. This study reported eight serologically confirmed brucellosis cases inPaholpolpayuhasenaHospital. All of them contacted goats. Most of them received doxycycline plus rifampicin and all were cured.